Usulan Perancangan Tata Letak Fasilitas pada Pembuatan Kulit Kebab Tortila Guna Meminimalisir Jarak Material Handling dan Meningkatkan Output Produksi (Studi Kasus: PT Tamma Robah Indonesia) - Prasetya, May Irvan Aji; Wati, Putu Eka Dewi Karunia (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT Tamma Robah Indonesia is a company operating in the manufacturing industry which produces kebab tortilla shells, the types of products produced by PT Tamma Robah Indonesia are TB (Large Tortilla), TS (Medium Tortilla), TM (Mini Tortilla), TC (Tortilla Catering). This research method uses the line balancing method which aims to obtain a smooth production flow in order to obtain high utility for facilities, labor and working time as well as simulating the production flow process, distance and increasing production output using flaxim software development to maximize the implementation of relayout. . Based on the results of the analysis of the research objectives carried out, it can be concluded that the line balancing calculation of the 4 products produced by PT Tamma Robah Indonesia selected the lowest Tortila Catering process distance with a cycle time of 130 seconds. /pcs, with 3 work stations, efficiency and delay 23%. and there are several proposed layouts that can minimize material handling distances.